The Effect of Corporate Governance Mechanisms on Initial Return on IPO Companies Listed on the Indonesia Stock Exchange - Aisyah, Sarah (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the effect of corporate governance mechanisms on initial returns in companies conducting IPOs on the Indonesia Stock Exchange for the 2019-2023 period. The phenomenon of underpricing in IPOs which increased significantly (61.2%) during this period became the main problem under study. Using an associative causal quantitative approach with secondary data that is time series and cross section, this study analyses 136 companies selected through purposive sampling. The independent variables studied include board gender diversity, board size, independent commissioners, and managerial ownership. The results show that board gender diversity, board size, and independent commissioners have no significant effect on initial return. However, managerial ownership has a significant positive effect. Simultaneously, the four variables have no effect on initial return with the ability to explain limited variation in initial return (R Square 7.6%). This study implies that in Indonesia, of the corporate governance aspects studied, only managerial ownership has a significant influence on IPO performance.